iConference 2014 Proceedings 2014
DOI: 10.9776/14308
|View full text |Cite
|
Sign up to set email alerts
|

Rumors, False Flags, and Digital Vigilantes: Misinformation on Twitter after the 2013 Boston Marathon Bombing

Abstract: The Boston Marathon bombing story unfolded on every possible carrier of information available in the spring of 2013, including Twitter. As information spread, it was filled with rumors (unsubstantiated information), and many of these rumors contained misinformation. Earlier studies have suggested that crowdsourced information flows can correct misinformation, and our research investigates this proposition. This exploratory research examines three rumors, later demonstrated to be false, that circulated on Twitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(60 citation statements)
references
References 13 publications
0
56
0
1
Order By: Relevance
“…The visibility produced through DV is unwanted (the target is typically not soliciting publicity), intense (content like blog posts, photos and video evidence can circulate to hundreds of thousands or even millions of users within a few days) and enduring (the vigilantism campaign may be the first item to appear when searching the individual's name, and may become a cultural reference in its own right). DV can be fuelled by the circulation of misinformation (Starbird et al 2014), such as when a target is misidentified as a suspect or offender. Moreover, there is evidence that such falsehoods circulate with greater volatility than truthful details (Lotan 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The visibility produced through DV is unwanted (the target is typically not soliciting publicity), intense (content like blog posts, photos and video evidence can circulate to hundreds of thousands or even millions of users within a few days) and enduring (the vigilantism campaign may be the first item to appear when searching the individual's name, and may become a cultural reference in its own right). DV can be fuelled by the circulation of misinformation (Starbird et al 2014), such as when a target is misidentified as a suspect or offender. Moreover, there is evidence that such falsehoods circulate with greater volatility than truthful details (Lotan 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Starbird et al examined the relationship between rumors and crowd correction on Twitter after the 2013 Boston Marathon Bombing [20], and Oh et al found that information from credible sources suppresses anxiety through an analysis of Twitter data using both quantitative and qualitative methods following the 2010 earthquake in Haiti [21].…”
Section: Discussionmentioning
confidence: 99%
“…Moving from broadcast television to newer media, over 20 million tweets about the bombing, many sent from smartphones at the scene, flooded Twitter. These included ostensibly factual information 7 using hashtags like #breaking, #manhunt, and #mitshooting, as well as expressions of support and solidarity like #prayforboston and #bostonstrong (Starbird et al 2014). While the "customary places" for conversation may have changed since Durkheim's time, the conversation clearly still occurs and the result appears to be the same: public indignation and, eventually, community solidarity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Notably, a great deal of misinformation was found in these tweets(Starbird et al 2014) 44Brenner et al…”
mentioning
confidence: 99%